Когнітивне моделювання як метод якісного аналізу ризиків ІТ-проектів - Онищенко, І. І. (НТУ "ХПІ", 2016)
Пропонується побудова когнітивної моделі ризиків проекту в галузі інформаційних технологій в рамках якісного аналізу ризиків, як метод додаткової оцінки рангу ризику, для визначення характеристик взаємозв‘язку між ними. Запропонована когнітивна модель відображає взаємозв‘язки між ризиками ІТ-проекту з проведенням оцінки негативного та позитивного впливу певних ризиків на решту ризиків проекту впровадження автоматизованої CRM-системи.

The example project implementing automated CRM-system demonstrated the possibility and features of cognitive modeling in the qualitative analysis of project risks to determine their additional features. Proposed construction of cognitive models of project risks in information technology within the qualitative risk analysis, additional assessments as a method of ranking risk to characterize the relationship between them. The proposed cognitive model reflecting the relationship between the risk of IT project to assess the negative and the positive impact of certain risks for the remaining risks of project implementation of the automated CRM-system. The ability to influence the risk of fact of other project risks can increase the priority of risk with low impact on results due to its relationship with other project risks.
Cognitive modeling as a method of qualitative analysis of IT projects
Keywords: управління ризиками; когнітивна модель; інформаційні технології; ранг ризику; risk; risk management; cognitive model; qualitative analysis; ranking; IT project